A revitalização da Brinquedoteca Universitária – Campus Altamira - UFPA - ROCHA, Andressa Dutra Nascimento (2023)
The toy libraries enable a set of social and cognitive developments in the child through play; games are developed to stimulate children's creativity, motor coordination, and logical thinking. The purpose of this article is to reflect on the experience of a supervised internship in non-school environments and, as students, the pedagogical practices in the space of the university toy library. As methodology, the qualitative approach was used, which began with students of the course of pedagogy through meetings, visits to space, collection, production of materials, collections, and content analysis. Thus, the revitalization was done with the support of the local community, providing a new space of joy and curiosity in which children could be welcomed. The space is geared for playful, creative, and learning actions.